Exit and voice: diaspora population and national development in Nigeria - Onyekachi E. Nnabuihe; Kelvin Ashindorbe; Oluwasola Oni; David Kosoko (Cogent Social Sciences, 2024)
This article interrogates the role of the Nigerian Diaspora in contributing financial and intellectual remittances for national development. It does so because conventional diaspora studies have focused on how various diaspora populations adapt to the social, economic, and political realms in the countries of settlement even as they seek to maintain their own traditions and cultures. Recent developments indicate Diasporas have played prominent roles in the political, social, and economic development of their countries of origin. As a result, it becomes crucial to integrate the role of the Diaspora in contributing not just financial but also intellectual remittances to enhance national development. This is because intellectual remittances are critical for institution building and addressing leadership deficit which will in turn channel financial remittances into proper national development agenda. Yet, this is too often neglected in the extant literature. Relying on the diaspora option theory and Hirschman’s exit, voice and loyalty theory, with data gleaned from a structured questionnaire survey, interviews, institutional reports, and other secondary sources, this article explores how diaspora communities serve as critical bridges that facilitate national development through financial and intellectual remittances. The study revealed that whereas financial remittance is important for addressing development gaps, it becomes more forceful when combined with other forms of remittances such as intellectual and social remittances.